2015
DOI: 10.1093/bja/aev299
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of stroke volume optimization during elective major abdominal surgery in patients stratified by aerobic fitness

Abstract: ISRCTN21597243.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…Fluid administration may also cause a relative, but not absolute, reduction in hemoglobin (Hb) concentration (“dilutional anemia”). Such iatrogenic hemodilution may cause a paradoxical decrease in DO2 due to the resulting decrease in Hb concentration, as observed in patients who have received more colloids as part of perioperative goal-directed therapy (GDT) [6] and in critically ill patients who did [7] or did not [8] increase their cardiac output following fluid loading. In patients in septic shock who received large amounts of fluids as part of the original early GDT protocol, a decrease of 30% in hematocrit was uniformly observed 3 h into the resuscitation, possibly explaining the very high incidence of blood transfusions in this group of patients [9].…”
Section: The Effect Of Fluid Administration On the Hemoglobin Concentmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluid administration may also cause a relative, but not absolute, reduction in hemoglobin (Hb) concentration (“dilutional anemia”). Such iatrogenic hemodilution may cause a paradoxical decrease in DO2 due to the resulting decrease in Hb concentration, as observed in patients who have received more colloids as part of perioperative goal-directed therapy (GDT) [6] and in critically ill patients who did [7] or did not [8] increase their cardiac output following fluid loading. In patients in septic shock who received large amounts of fluids as part of the original early GDT protocol, a decrease of 30% in hematocrit was uniformly observed 3 h into the resuscitation, possibly explaining the very high incidence of blood transfusions in this group of patients [9].…”
Section: The Effect Of Fluid Administration On the Hemoglobin Concentmentioning
confidence: 99%
“…Other RCTs have also reported that patients in the GDT group, who received significantly more colloid boluses, received significantly more blood transfusions [12, 13] and had significantly higher blood loss [13] compared to the standard therapy group. In another study, the administration of more colloids led to lower Hb and DO2 values at the end of surgery (hemodilution being the responsible mechanism according to the authors themselves), and an associated trend of increased intraoperative blood loss [6]. In another prospective study comparing patients before and after the adoption of a GDT protocol, a pulse pressure variation-guided protocol was associated with less fluid administration, significantly higher Hb values after surgery, less blood transfusions, and decreased morbidity [14].…”
Section: The Potential Impact Of Hemodilution On Blood Transfusionsmentioning
confidence: 99%
“…Even in the latest trials, the addition of flow monitoring to routine monitoring does not appear to have had much benefit as far as either reduction in mortality or complications are concerned, and it is still around 5% in the elderly surgical population. (3,5,6) Although there is now evidence to suggest that the use of individual new monitors SIGNA VITAE 2016; 11(SUPPL 2): [22][23][24][25][26][27] can influence outcome, it will only be their combination that will radically improve the perioperative management on outcome of high-risk surgical patients. (7,8) Blood Pressure and Flow monitoring as part of a multimodal monitoring strategy Most anaesthetists will try and maintain mean arterial pressure (MAP) during surgery within about 20% of the pre-induction value.…”
Section: New Monitoring Technology and Its Use In The Operating Roommentioning
confidence: 99%
“…(15) Post induction measurement of CO greatly underestimates the true resting CO/DO2 and therefore any intervention which is supposedly designed to "optimise stroke volume" (whatever that means) rather than maintain pre-induction CO/DO2 will be flawed and may result, as above, in unnecessary excess fluid and Na+ administration without improving outcome in high-risk patients _ENREF_15. (6,15) …”
Section: Cardiac Output Changes Fol-lowing Induction and Mainte-nancementioning
confidence: 99%
“…Lai et al measured cardiac output in patients undergoing major abdominal surgery, but this was not obtained at baseline for cardiovascular optimization in the intraoperative period [1]. Current studies show significant cardiovascular parameters changes that occur during period of anaesthesia maintenance [2 -5].…”
Section: Introductionmentioning
confidence: 99%